Litterfall, Throughfall and Stemflow in Acacia Mangium Stands on Tin Tailings and Their Effects on Soil Chemical Properties - Indu, Indreshwar Prasad (1995)
Acacia mangium has been planted on ex-tin tailing areas to improve soil fertility. The return of macro nutrients from A. mangium and their effects on the soil chemical properties is however not well understood. The main objective of this study is to compare the effects of macro nutrient input via A. mangium litter, throughfall and stemflow on soil chemical properties of mineral and ex- tin mining soils. The first study area located in mineral soil situated in Universiti Pertanian Malaysia farm consists of an A. mangium covered plot (AMA) and a grass covered plot (GCA). The second study area on ex-tin mine soil located in Semenyih, Selangor, consists of an A. mangium covered plot (AMB) and a grass covered plot (GCB). The total annual litter production for AMA is 872.51 g/m2 and 741.18 g/m2 for AMB. The litter production of AMA is significantly (P<0.01) higher than that of AMB.